Mechanistic understanding of rapid gelation of silk fibroin using a biosurfactant – sophorolipid - Dubey, Parul; Nawale, Laxman; Sarkar, Dhiman; Nisal, Anuya; Prabhune, Asmita (National Science Day, At CSIR-NCL, 2015)
3D polymeric hydrogels find use in biomedical applications as scaffolds and drug delivery vehicle • Silk fibroin a structural protein is a promising candidate (excellent thermo-mechanicals, biocompatibility, biodegradability) • Sophorolipid (SL)-a biosurfactant is known to exhibit antimicrobial, anti cancerous and cell differentiating. • Use of SL as gelling agent can enhance the applicability of SF hydrogels • SF-SL scaffolds obtained by lyophilization of hydrogels can find application in tissue regeneration

Sophorolipid assisted tunable and rapid gelation of silk fibroin to form porous biomedical scaffolds - Dubey, Parul; Nawale, Laxman; Sarkar, Dhiman; Nisal, Anuya; Prabhune, Asmita (RSC Advances, 2015)
Three dimensional polymer hydrogels, based on both natural and synthetic polymers, are increasingly being used as scaffolds and drug delivery vehicles for biomedical applications. Fibrous protein, silk fibroin (SF), obtained from the Bombyx mori silkworm is a promising candidate in this area. However, SF has a long gelation time of about a few weeks that can only be reduced by non-physiological treatments (e. g. high temperature, ultrasonication and low pH) or by addition of a chemical and non-biodegradable polymer and/or surfactant. We report here accelerated gelation of SF under physiological conditions using a biosurfactant, sophorolipid (SL) as a gelling agent. SL and SF are completely miscible and form a very clear solution upon mixing. Hence it is interesting to see that this clear solution gels in a time span of just a few hours. The hydrogels so formed have pore architecture, porosities and mechanical stability ideally suited for tissue culture applications. Here we also demonstrate that mouse fibroblast cells not only adhere to but also extensively proliferate on these SF-SL scaffolds.

UV-assisted size sampling and antibacterial screening of lantana camara leaf extract synthesized silver nanoparticles - Singh, Pradeep Kumar; Bhardwaj, Kirti; Dubey, Parul; Prabhune, Asmita (RSC Advances, 2015)
Green route synthesized silver nanoparticles are extremely toxic to multidrug resistant bacteria and have widespread applications in biomedical science. If the silver reducing weed extract possesses antimicrobial properties then it can additionally contribute to the medicinal activity. Herein, we present a synthesis of silver nanoparticles by using the weed plant Lantana camara's leaf extract. This study shows an easy, quick and cost-effective route to silver nanoparticle synthesis. Size controlled synthesis of Ag-0 nanoparticles is studied and discussed based on optical absorption, photoluminescence, dynamic light scattering (DLS), zeta potential, infrared spectroscopy, X-ray diffraction measurements, FE-SEM and TEM analysis. The synthesis of silver nanoparticles via this green approach shows very high antibacterial activity against E coli (Gram -ve) and S. aureus (Gram +ve) bacteria at a very low concentration (50 ppm Ag nanoparticles). Use of such eco-friendly nanoparticles may open a door for a new range of bactericidal agents.

Silk fibroin-sophorolipid gelation: deciphering the underlying mechanism - Dubey, Parul; Kumar, Sugam; Aswal, Vinod K.; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Prabhune, Asmita; Nisal, Anuya (Biomacromolecules, 2016)
Silk fibroin (SF) protein, produced by silkworm Bombyx mori, is a promising biomaterial, while sophorolipid (SL) is an amphiphilic functional biosurfactant synthesized by nonpathogenic yeast Candida bombicola. SL is a mixture of two forms, acidic (ASL) and lactonic (LSL), which when added to SF results in accelerated gelation of silk fibroin. LSL is known to have multiple biological functionalities and hence hydrogels of these green molecules have promising applications in the biomedical sector. In this work, SANS, NMR, and rheology are employed to examine the assembling properties of individual and mixed SLs and their interactions with SF to understand the mechanism that leads to rapid gelation. SANS and NMR studies show that ASL assembles to form charged micelles, while LSL forms micellar assemblies and aggregates of a mass fractal nature. ASL and LSL together form larger mixed micelles, all of which interact differently with SF. It is shown that preferential binding of LSL to SF causes rapid unfolding of the SF chain leading to the formation of intermolecular beta sheets, which trigger fast gelation. Based on the observations, a mechanism for gelation of SF in the presence of different sophorolipids is proposed.

Anti-proliferative effect of novel primary cetyl alcohol derived sophorolipids against human cervical cancer cells HeLa - Nawale, Laxman; Dubey, Parul; Chaudhari, Bhushan; Sarkar, Dhiman; Prabhune, Asmita (Plos One, 2017)
Sophorolipids (SLs) are glycolipid biosurfactants that have been shown to display anticancer activity. In the present study, we report anti-proliferative studies on purified forms of novel SLs synthesized using cetyl alcohol as the substrate (referred as SLCA) and their anticancer mechanism in human cervical cancer cells. Antiproliferative effect of column purified SLCA fractions (A, B, C, D, E and F) was examined in panel of human cancer cell lines as well as primary cells. Among these fractions, SLCA B and C significantly inhibited the survival of HeLa and HCT 116 cells without affecting the viability of normal human umbilical vein endothelial cells (HUVEC). The two fractions were identified as cetyl alcohol sophorolipids with non-hydroxylated tail differing in the degree of acetylation on sophorose head group. At an IC50 concentration SLCA B (16.32 mu g ml(-1)) and SLCA C (14.14 mu g ml(-1)) blocked the cell cycle progression of HeLa cells at G1/S phase in time-dependent manner. Moreover, SLCA B and SLCA C induced apoptosis in HeLa cells through an increase in intracellular Ca2+ leading to depolarization of mitochondrial membrane potential and increase in the caspase-3, -8 and -9 activity. All these findings suggest that these SLCAs could be explored for their chemopreventive potential in cervical cancer.

pH dependent sophorolipid assemblies and their influence on gelation of silk fibroin protein - Dubey, Parul; Kumar, Sugam; Ravindranathan, Sapna; Vasudevan, Sahana; Aswal, Vinod K.; Rajamohanan, Pattuparambil R.; Nisal, Anuya; Prabhune, Asmita (Materials Chemistry and Physics, 2018)
Sophorolipid (SL), a bio-derived surfactant is an excellent gelling agent for natural fibrous protein, silk fibroin (SF) leading to potential biomedical applications. Interaction of SF with SL has been shown to accelerate the formation of hydrogel with the rate being dependent on the form of SL used. Here, we examine the effect of pH on SL-SF interaction and gel formation by employing rheology, fluorescence spectroscopy, SANS and NMR. The results indicate that the size of SL assemblies decrease as pH increases from acidic to alkaline and significantly impacts the association of SL and SF. The association of SF and SL is mainly via hydrophobic interactions, with the SL molecules forming bead like structures along the SF chain. The increased charge on the acidic form of SL at higher pH results in greater repulsion between acidic SL molecules, which are bound to the hydrophobic sites of SF, leading to rapid chain unfolding and subsequent gelation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Assemblies; Nuclear magnetic resonance spectroscopy; pH; Silk fibroin; Small angle neutron scattering; Sophorolipid